Taxation and public spending in Peru 2000-2018 - Pingo Zapata, Manuel E. (2021)
In general, when the river flow increases, a scour phenomenon will occur, in which the substructure of the bridge, be it abutment and / or piers, will be affected, resulting in a partial or total collapse of the structure. All of the above is the key to achieving our research objectives, which is to carry out an evaluation and protection design against the hydraulic scour process of the Unocolla bridge in the city of Juliaca, Puno. The population will be the Unocolla bridge and the sample will be a substructure of the bridge. The method used is applied and its design is pure experimental, using quantitative methods, in which the research problem is described as realistic results. To determine the scour effects, topographic, hydrological and sedimentological information was collected to later carry out hydraulic modeling in the Hec-Ras program. Scour depths were determined in reference to pillars, determining in pillar 1 scour depth 1.2 m, in pillar 2 scour depth 2.46 m, in pillar 3 scour depth 1.2 m, in pillar 4 scour depth 1.2 m, for which the castling process is proposed as an alternative solution.